Pulse Density Modulation Based Series Resonant Inverter Fed Induction Heater System - S. Jaanaa Rubavathy; P. Murugesan (International Journal of Power Electronics and Drive Systems (IJPEDS), 2018)
This paper deals with implementation of a multi-output Series Resonant Inverter(SRI) for induction heating applications, which uses pulse density modulation(PDM) control for full bridge Series resonant inverters for output voltage and power control. It ensures better efficiency performances than conventional control strategies. The proposed converter can be considered as a two output extension of a full bridge inverter. This full bridge inverter can control the two outputs, simultaneously and independently, up to their rated powers, which reduces the usage of number of components as compared with conventional method. It also ensures higher utilization of switches used for its operation. A two output full bridge series resonant inverter is simulated and implemented. The Experimental results are compared with the simulation results.